Measles antibody response in vaccinated children - Evliyaoğlu, Nurdan; Altıntaş, Derya; Kılıç, N. Banu; Alhan, S. Emre; Önenli, Neslihan; Güneşer, Seval; Bahçebaşı, Talat (The Turkish Journal of Pediatrics, 1996)
The incidence of measles has declined in our country since the routine administration of measles vaccination was initiated. However, measles outbreaks have been observed even among previously vaccinated children. The objective of this study was to evaluate the measles antibody response of children vaccinated at nine months of age. Measles-specific IgG antibodies were determined by enzyme-linked immunosorbent assay. Of 345 children tested, 20.3 percent were immunologically measles-susceptible. When measles-specific antibody titers were analyzed with respect to the elapsed time since prior vaccination, the result was found to be insignificant (p>0.05). These data suggest that the underestimated seropositivity rate of measles antibody may be related to both primary vaccine failure and inappropriate vaccination age.